Pengaruh Kepemimpinan, Disiplin Kerja Dan Kompensasi Terhadap Kinerja Karyawan Lembaga Pendidikan Muhammadiyah Di Kartasura - Akbar, Tsaqib Faizal, Muzakar Isa, SE., M.Si (2016)
a hoped-for goal from the study is to know the influence of kepemimpimam , discipline work and compensation of the performance of employees educational institutions muhammadiyah in kartasura .In addition researchers also aims to know the influence of together of the three variable independent and he knows variables most influential or dominant .The kind of research this is research quantitative for using data that requires calculation .To research this time the sample collection using a method of solvin with the estimate wrongdoing ( e ) 0.05 so that the number of samples to be taken 75 an employee ( teachers and employees institution ) of the total object research . The method of analysis lab data it uses test an instrument consisting of the validity and reliabelitas .Next use test the assumption classical consisting of the trial normality , test multikolonieritas and the heteroskedastisitas .And last use the hypothesis consisting of the analysis of multiple regression , the f , test t and the determination .In conducting a data analysis , researchers used assistance successor program computer statistics spss 20 to ease the project. Based on the results of calculations spss 20 the results the validity of every item-item statement in all the variables expressed valid because it r count & gt; r table as alpha 0.05, so that all statement can be used or analyzed.Next the results of the reliabelitas who tested consistency each variable all showed results reliabel with cronbach's alpha & gt; 0.60 so data chief trustworthy.While the results of the normality by using test kalmogrov smirnov test showed data to research this normal with the p & gt; 0.05.Test multikolonieritas shows the tolerance & gt; 0.1 and vif & lt; 10 which means does not occur multikolonieritas.Test heteroskedastisitas who uses the method glegser, the results sig.T or significant & gt; 0.05 which means not constant. The results of the analysis of multiple regression three prediktor to get equation y = 6.037 + 0,222x1 + 0,383x2 + 0,133x3 .Test f the results probability significant 0,000 & lt; 0.05 ho were rejected and ha received so variables on the this research have an together .The results of the t obtained variable leadership significant showed the probability significant 0,039 & lt; 0.05 ho were rejected and ha accepted , variable discipline work probability significant 0,001 & lt; 0.05 ho were rejected and ha accepted , and variable compensation insignificant with probabilities significant 0,352 ho received and ha rejected .The results of the determination showed r2 of 0,270 or 27,0 % .The rest can be explained by other variables that no in the model . Password: of employee performance , leadership , discipline work and compensation .